1991
DOI: 10.1128/iai.59.10.3722-3739.1991
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of adherence of enteroaggregative Escherichia coli to human and animal mucosa

Abstract: An Escherichia coli strain (serotype 0127a:H2) that had been isolated from a child with diarrhea in Thailand and that was negative for the virulence factors of the four categories of diarrheagenic E. coli (enterotoxigenic, enteropathogenic, enteroinvasive, and enterohemorrhagic) and that showed an aggregative pattern of adherence to HeLa cells was investigated for adherence to native or Formalin-fixed human and animal mucosa. The hemagglutinating activity and adherence ability of the bacteria were resistant to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
52
2

Year Published

1992
1992
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 42 publications
8
52
2
Order By: Relevance
“…These results are in tandem with recent reports which are beginning to indicate that the pathogenicity of EAggEC is mediated by a toxin because they do not induce the attaching and effacing lesion characteristic of EPEC [14]. Further, experimental EAggEC infection in isolated rabbit and porcine intestinal loops appear to indicate the EAggEC may elaborate a toxin that damages enterocytes [15]. It has recently been demonstrated that EAggEC elaborate a low molecular mass partially heat-stable enterotoxin which induces ion transport alterations consistent with a secretory response [3].…”
Section: Discussionsupporting
confidence: 83%
“…These results are in tandem with recent reports which are beginning to indicate that the pathogenicity of EAggEC is mediated by a toxin because they do not induce the attaching and effacing lesion characteristic of EPEC [14]. Further, experimental EAggEC infection in isolated rabbit and porcine intestinal loops appear to indicate the EAggEC may elaborate a toxin that damages enterocytes [15]. It has recently been demonstrated that EAggEC elaborate a low molecular mass partially heat-stable enterotoxin which induces ion transport alterations consistent with a secretory response [3].…”
Section: Discussionsupporting
confidence: 83%
“…Knutton et al (1992) showed that 44 different EAggEC isolates adhered to human adult colonic mucosa but none of six isolates adhered to ileal mucosa. Yamamoto et al (1991), using a single isolate of EAggEC, found low levels of adhesion to native jejunal and ileal mucosa and high levels of adhesion to formalin-fixed colonic mucosa. The same group also investigated the adhesion of EAggEC to native unfixed jejunal tissue from a child.…”
Section: Haemagglutination and Autoagglutinationmentioning
confidence: 93%
“…Knutton et al (1992) identified an isolate that showed the typical aggregative phenotype but did not produce the characteristic fibrillar bundles on EM and did not hybridize with a DNA probe. Others have identified EAggEC isolates that do not hybridize with probes that have high specificity for the aggregative phenotype (Baudry et al 1990;Yamamoto et al 1991;Debroy et al 1994a). Czeczulin et al (1995) probed EAggEC strains with probes for both AAF/I and AAF/II fimbriae, and have found strains that do not hybridize with either probe, suggesting the existence of more aggregative adherence-associated fimbriae.…”
Section: Characterization Of Fimbriae Mediating Aggregative Adherencementioning
confidence: 99%
“…Apart from the HeLa cell adherence properties (Ad), the EAggEC strains usually exhibit mannose-resistant hemagglutination (MRHA) activities towards erythrocytes of human and certain other species [8]. Further, Yamamoto et al [9] have demonstrated unique adherence charac-teristics of these strains to both native and formalin-fixed human and animal mucosa. The cellular adherence properties of EAggEC appear to correlate well with the expression of fimbriae encoded by 55-65 MDa plasmids [8].…”
Section: Introductionmentioning
confidence: 99%